New Regulations on Supplementary Income for Transfer Recipients: a Great Challenge - Kerstin Bruckmeier; Jürgen Wiemers (Wirtschaftsdienst)
Abstract In its coalition agreement, the German government proposes a reorganisation of the rules of earned income to be considered as a means test of basic income. In doing so, it takes up a frequently voiced criticism of the design of the basic income support for job-seekers under Book II of the Social Code. In recent years, researchers have called for a strengthening of (monetary) incentives to work, especially to take up employment with higher weekly working hours. In this paper, we summarise potential effects of such a reform on labour supply, the income distribution and the government budget in the context of a complex welfare system characterised by a high level of benefit non-take-up.